2007
DOI: 10.4081/ijas.2007.1s.509
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of Mediterranean buffalo milk fat

Abstract: The purpose of this research was to investigate the variation in fatty acid composition of milk fat from four buffalo (Bubalus bubalis) herds under different feeding management and ration composition. Changes in milk fatty acid composition were monitored on a weekly basis. Saturated fatty acids (65.5%) predominated in buffalo milk fat; monounsaturated and polyunsaturated fatty acids were 27.0% and 4.5%, respectively. Of saturated fatty acids, the content of palmitic acid was the highest (30.6%) followed by ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 4 publications
8
23
4
1
Order By: Relevance
“…In addition, the percentages of polyunsaturated fatty acids (PUFA) were close to each other in the B-LFS and C-LFS samples although our results were in contrast with those observed by Varricchio et al (2007), because they found that buffalo milk fat contained higher amounts of SFA and lower amounts of unsaturated fatty acids than cow milk fat. However, results of the previous authors were from other breeds which are different from the breed of Egyptian buffalo animals.…”
Section: Effects Of Ph Values On the Fac Of B-lfs And C-lfscontrasting
confidence: 68%
“…In addition, the percentages of polyunsaturated fatty acids (PUFA) were close to each other in the B-LFS and C-LFS samples although our results were in contrast with those observed by Varricchio et al (2007), because they found that buffalo milk fat contained higher amounts of SFA and lower amounts of unsaturated fatty acids than cow milk fat. However, results of the previous authors were from other breeds which are different from the breed of Egyptian buffalo animals.…”
Section: Effects Of Ph Values On the Fac Of B-lfs And C-lfscontrasting
confidence: 68%
“…This does not meet the expectation for diminished biohydrogenation as a result of lower pH (Talpur, 2007) in response to silage feeding (Jalč et al, 2013), but in the buffaloes this is confirmed. In the present study the values of stearic acid in the buffalo milk are higher in comparison not only to the bovine milk but also to other results for the Bulgarian Murrah (Naydenova, 2005;Mihaylova and Peeva, 2007) and other breeds Varricchio et al, 2007). While in bovine milk worldwide the content of C18:0 varies in wide ranges (Samková et al, 2012;Beyero et al, 2015), on national scale the findings concerning mostly herds of Bulgarian Black and White cattle and other breeds are quite consistent (Mihaylova, 2007;Dimitrov, 2007), including our results.…”
Section: Discussionmentioning
confidence: 53%
“…In fact, a possible dilution effect of milk protein was not observed as milk production increased. Average basal values of fat (7.43-7.71%, Table 1) were below the normal concentration (8.3%) reported by Varrichio et al (2007). The lower milk fat content after oil supplementation (L= -1.64g/100g and H= -2.49g/100g, Table 1) could be explained in part by a dilution effect as milk yield increased (Table 1) and was not reported for confined buffaloes supplemented with soybean oil at a rate of 2.21% of total DM intake (Oliveira et al, 2009).…”
Section: Discussionmentioning
confidence: 96%